2018
DOI: 10.3389/fphar.2018.00741
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Trichloroethylene on Rat Neuroprogenitor Cells

Abstract: Trichloroethylene (TCE) is a common volatile organic solvent which is considered as an ubiquitous environmental pollutant. It is claimed to be a developmental neurotoxicant. Our group evaluated previously its impact on three-dimensional neurospheres in vitro. The current work aims to investigate the neurotoxic effects of a lower concentration of TCE on the same system. To perform the experiment, neural progenitor cells were obtained from the brains of nine newborn rats. Afterward, these cells were cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Among newer studies identified in the EPA literature search, developmental neurotoxicity was indicated by increased locomotor and exploratory activities were observed following drinking water exposures to mice during nervous system development (Blossom et al, 2013), however these effects were not consistently dose-responsive. A follow-up study from that laboratory (Blossom et al 2016) reported inflammation-mediated cerebellar oxidative stress and increased locomotor activity following gestational TCE exposure in autoimmune-prone mice, while another study demonstrated that TCE reduces cell viability and inhibits differentiation of neural progenitor cells in culture (Salama et al 2018). In addition to the results from (Blossom et al 2016), various indicators of developmental immunotoxicity were also observed in another MRL +/+ mice study (Gilbert et al 2014).…”
Section: Developmental Immunotoxicitymentioning
confidence: 99%
“…Among newer studies identified in the EPA literature search, developmental neurotoxicity was indicated by increased locomotor and exploratory activities were observed following drinking water exposures to mice during nervous system development (Blossom et al, 2013), however these effects were not consistently dose-responsive. A follow-up study from that laboratory (Blossom et al 2016) reported inflammation-mediated cerebellar oxidative stress and increased locomotor activity following gestational TCE exposure in autoimmune-prone mice, while another study demonstrated that TCE reduces cell viability and inhibits differentiation of neural progenitor cells in culture (Salama et al 2018). In addition to the results from (Blossom et al 2016), various indicators of developmental immunotoxicity were also observed in another MRL +/+ mice study (Gilbert et al 2014).…”
Section: Developmental Immunotoxicitymentioning
confidence: 99%
“…The neurotoxicity, hepatotoxicity, and development toxicity of toluene and xylene has been well documented [ 6 , 7 ]. Trichloroethylene, as a developmental neurotoxicant, can not only disturb the cell viability and induce apoptosis and necrosis, but also affect the neural proliferation, neurite outgrowth, and differentiation [ 8 ]. Additionally, the previous study has documented the toxic effects of certain glyphosate-based formulations (Roundup FG and Mon 8750) on earthworms through lethal toxicity, lysosomal destabilization, and DNA damage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%